Hospital-Acquired Urinary Tract Infection, Microbial Causative Agents and Antibiotic Resistance Pattern in Southern Iran: A Prospective Study - Farzaneh Dehghan (Journal of Global Pharma Technology, 2017)
Background Objective: Antimicrobial resistance is a problem in hospital-acquired urinary tract infection (UTI), and is the most frequent nosocomial infection. This study was carried out to determine the prevalence of Hospital-acquired Urinary Tract Infection (HAUTI)  a etiological microorganisms and their antimicrobial resistance to commonly used antibiotics. Methods: This cross-sectional study was performed in a referral state general hospital in Bandar abbes, Southern Iran between January, 2014 and December, 2015. All cases   admitted to the different wards   of Shahid Mohammadi Hospital and recognized as symptomatic and asymptomatic   HAUTIs, after 48 h of admission, and those who were readmitted to the hospital because of a UTI up to 48 h after discharge from the hospital were included as the targeted population. According to the checklist, the risk factor and demographic information of these patients were recorded. The identification of isolated microorganisms was done by standard microbiological test, then antimicrobial susceptibility testing of all bacterial isolates was performed by disk diffusion method and statistical analysis was done using SPSS software version 20.0.Results In this study, 1.57% of the 19,768 hospitalized patients   acquired   HAUTI. The most commonly isolated gram negative bacteria  are Escherichia coli 26.7%(82), followed by Acinetobacter baumannii  15.3%(47) and among gram positive organisms, it was Candida spp 23.5%(72). Gram negative bacteria were most resistant to Ceftriaxone, non-fermented bacteria were most resistant to Cefazol in, Cotrimoxazole and Nalidixic acid, Staphylococcus spp were resistant to Ampicillin, Enterococcus fecalis was resistant to Gentamicin and Nalidixic acid while Streptococcus agal actie did not show any resistance pattern .Conclusions The results of this study are indicative of a big challenge about the prevalence of multi-drug resistant bacteria in the studied hospital that limits therapeutic options, if infection control policy and continuous monitoring of ESBL bacteria are not used.Keywords: Antibiotic resistance, Hospital-acquired Urinary Tract Infection.